2010
DOI: 10.1016/j.leukres.2010.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide and ascorbic acid demonstrate promising activity against primary human CLL cells in vitro

Abstract: The compromised antioxidant defense system in chronic lymphocytic leukemia (CLL) suggested a potential use for Reactive Oxygen Species (ROS) generating Arsenic Trioxide (ATO) and Ascorbic Acid. While both ATO and ascorbic acid mediated cytotoxicity in CLL B cells as single agents, the efficacy of ATO is enhanced by ascorbic acid. This effect is dependent on increased ROS accumulation, as pretreatment of B-CLL cells with a glutathione reducing buthionine sulfoximine or catalase inhibiting aminotriazole, enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 36 publications
(32 reference statements)
5
16
0
Order By: Relevance
“…Our result is similar to the reports that vitamin C enhances ATO-induced cytotoxicity in multiple myeloma cells (50)(51)(52), leukemia cells (53,54) and hepatocellular carcinoma cells (26). Therefore, vitamin C plays a role as a prooxidant rather than antioxidant in ATO-treated cells including HPF cells and it can be used with ATO for treatment of cancer including hematological malignancies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our result is similar to the reports that vitamin C enhances ATO-induced cytotoxicity in multiple myeloma cells (50)(51)(52), leukemia cells (53,54) and hepatocellular carcinoma cells (26). Therefore, vitamin C plays a role as a prooxidant rather than antioxidant in ATO-treated cells including HPF cells and it can be used with ATO for treatment of cancer including hematological malignancies.…”
Section: Discussionsupporting
confidence: 90%
“…The intracellular GSH content has a decisive effect on ATO-induced apoptosis (26,(30)(31)(32). In addition, BSO or vitamin C enhances GSH depletion in ATO-treated cells (26,33,50,54,61). Likewise, ATO dose-dependently increased the number of GSH-depleted cells in HPF cells.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1A shows that ATO significantly induced apoptosis in a dose-dependent manner, confirming previous reports (19)(20)(21)(22). All samples tested were sensitive to ATO, independently of the clinical stage, the ZAP-70/ CD38 expression, or whether they had been frozen or were freshly isolated.…”
Section: Ato Induces Apoptosis Of B-cll Cells But Not Of Normal Pblsupporting
confidence: 87%
“…In analyses of a small number of B-CLL samples (18) or long exposure times (19), ATO was shown to induce apoptosis of B-CLL cells, concomitant with downregulation of Bcl-2. ATO also induced ROS generation and significantly enhanced the cytotoxic activity of 2-methoxyestradiol and ascorbic acid on B-CLL samples (20,21). It was recently reported that ATO preferentially induced apoptosis in B-CLL cases with unfavorable prognosis (22).…”
mentioning
confidence: 93%
“…However, high ROS levels can also mediate cell death [5]. ROS generating arsenic trioxide in combination with ascorbic acid efficiently kills CLL cells [6]. ROS increase through inhibition of key antioxidant enzymes such as superoxide-dismutase (SOD) also induces CLL cell death [7].…”
Section: Introductionmentioning
confidence: 99%